Human-Centered Organizational Culture in the Global Workplace: Strategic Approaches, Trends, and Practical Models - Barabanova, Yelena; Tyulyupergeneva, Raushan; Nazyrova, Larissa; Ladzina, Natalya; Bekbayeva, Malika (Ital Publication, 2025)
Amid accelerating global transformations, the need to reconsider human resource management strategies through the lens of human-centricity is becoming increasingly urgent. This study aims to examine the systemic implementation of human-centered organizational culture within international labor contexts, with a focus on enhancing employee well-being, adaptability, and organizational resilience. A mixed-methods approach was employed, combining comparative policy analysis, content analysis of regulatory documents, and empirical case studies. The empirical sample included 320 employees from multinational companies across four sectors (education, IT, healthcare, and manufacturing). The findings revealed statistically significant improvements following the implementation of the proposed model: autonomy increased from 5.48 to 5.86 (p = 0.012), competence from 5.33 to 5.61 (p = 0.038), and relatedness from 5.07 to 5.58 (p = 0.004). Positive emotion expression scores rose from 3.98 to 4.42 (p = 0.009), while the Human-Centeredness Index increased from 4.18 to 4.71 (p = 0.002). These results underscore the limitations of hierarchical management models and highlight the value of flexible, emotionally supportive systems. The scientific contribution of the study lies in the typologization of human-centric management models and the empirical validation of a scalable integration framework that combines emotional intelligence development, inclusive feedback cycles, and leadership support. This model provides a strategic foundation for building sustainable, inclusive, and ethically grounded organizational environments.